PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GENIALLY BERORIENTASI SALINGTEMAS PADA MATERI EKOSISTEM - Halimatussyakdiah; Aida Fitriani Sitompul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Biology learning on ecosystem material still faces various obstacles, particularly the limited use of interactive learning media, which affects student engagement and learning outcomes. This study aimed to develop Genially-based interactive learning media oriented to the Salingtemas (Science, Environment, Technology, and Society) approach on ecosystem material that meets the criteria of validity, practicality, and effectiveness. This research employed the Research and Development (R&D) method using the ADDIE model, covering the Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at SMA Negeri 1 Percut Sei Tuan involving 36 students of class X-4. Data were collected through expert validation sheets, teacher and student response questionnaires, and pretest-posttest instruments, then analyzed descriptively along with the Paired Sample t-test and N-Gain analysis. The results showed validation scores of 87.5% from material experts, 92.2% from media experts, and 89.0% from language experts, all in the highly valid category. The practicality test yielded 95.71% from teachers and 86.19%-86.67% from students across the trial stages, categorized as highly practical. The pretest mean increased from 48.69 to 87.75 on the posttest, with a Paired Sample t-test significance of 0.000 (<0.05) and an N-Gain of 0.7548 (high category). The developed media is therefore valid, highly practical, and effective for supporting Biology learning on ecosystem material.